Selected IFS publications and workshops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Selected IFS publications and workshops Tropical Mycorrhiza, Kuasi, Ghana, September 1978. Tropical Mycorrhiza Research, edited by P. Mikola, Oxford, Oxford University Press, 1980. £ 15.00. Yams-lgnames, Buea, Cameroon, October 1978. -...